Gonad development and hormone titres in Loggerhead Sea Turtles (Caretta caretta) in the NE Atlantic - Delgado, Cláudia Maria Neves (2010)
The study proposed to describe sexual development in pelagic stage loggerhead sea turtles Caretta caretta and compare this to hatchlings and adults. It is meant as an ontogenic approach, in order to understand reproductive development and population composition and their dynamics in the pelagic environment. The study focused on the pelagic loggerheads that are found in the waters offshore Madeira Island (Portugal) in the North-eastern Atlantic and use it as a developmental habitat. The innovating character of this work relied on the lack of any description regarding the gonad ontogenesis and reproductive development for the pelagic stage in any of the 7 existing sea turtle species, all of them in danger of extinction. Three methods were used to diagnose the sex of each juvenile individual and asses the level of reproductive development: (1) laparoscopy, (2) gonad biopsy and (3) the assessment of two sex steroids circulating levels, namely testosterone and estradiol. In order to cover all life stages and compare data obtained for the juvenile stage, hatchlings and nesting female adults were sampled at the nearest nesting rookery at Boa Vista Island in the Cape Verde Archipelago. Gonads from dead hatchlings were collected for gonad histology and blood was collected from nesting females for sex steroids assessment. Laparoscopies revealed to be a valid sexing method for the juvenile stage, since gonads are morphologically differentiated at these size classes. Moreover, laparoscopy was validated using gonad histology. Gonad histology of juveniles showed that gonads are already completely differentiated into ovaries or testes at the size classes examined, but development seems to be quiescent. Males present already developed seminiferous tubules with spermatogonia lining the interior of the seminiferous tubule. Female gonads present oocytes at different development stages, but only oocytes up to stage III were observed. The maximum oocyte diameter in each individual correlated with body size, suggesting that reproductive development is an on-going process in juvenile females. The circulating levels of both testosterone and estradiol in juveniles of both sexes were very low and consistently lower than the ones observed in the nesting females from Boa Vista Island. No bimodal distribution was found for any of the sex steroids analysed and thus circulating hormone levels were not a reliable tool for sexing juvenile individuals with a non-invasive technique. The ratio testosterone:estradiol did not show a bimodal distribution either. The levels of testosterone correlated with sea surface temperature. The fact that temperatures observed during this study were below 24ºC might have hindered a differential testosterone pattern between juvenile males and females. Sex ratios for this population were generated according to laparoscopy results and compared among years and size classes. An overall sex ratio of 2 females for each male was found, but they varied among size classes but not among years. Possible causes for the sex ratios observed are discussed. This study is a contribution to our knowledge on the pelagic stage of loggerhead turtles, namely on the population structure regarding sex ratio, which is a vital tool for implementing conservation strategies.